Variation order#44 Approval of non-schedule items' quantity and BoQ item for RCC bench & floor joints at stair - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the approval of non-schedule items' quantity and BOQ item for RCC bench & floor joints at stair of BRACU new campus building.